Larvicidal Activity of Streptomyces sp. Liquid Cultures Against Aedes aegypti Larvae - Ni Wayan Desi Bintari; Putu Ayu Parwati (Elkawnie: Journal of Islamic Science and Technology, 2022)
Abstract: The tropics have significant future challenges in controlling the vectors of dengue hemorrhagic fever. The occurrence of resistance to chemical control encourages the development of strategies based on biological control. This study aimed to test the larvicidal activity of Streptomyces sp. liquid culture toward A. aegypti larvae. The selection of Streptomyces as a bio-larvicide was carried out by a chitinase test. Chitinase-producing bacteria were cultivated in biomass culture. The study was conducted using a completely randomized design. The results of this study can be isolated 4 Streptomyces isolates from muddy soil. Among the isolates, Streptomyces sp.4 showed chitinolytic activity on in vitro tests; therefore, it was used for larvicidal activity. Based on the Duncan test result, Streptomyces sp.4 culture showed a significant effect on larval mortality compared to the negative control (p<0.05). The highest rate of larval mortality was found in the A6B1 treatment (34.35%). The results of the Probit test showed that the LD50 value of the Streptomyces sp.4 culture was 24.6±5.4 mL. Based on the in vivo test, showed that Streptomyces sp.4 liquid culture affected the mortality rate of A. aegypti larvae and was significantly different from the negative control (p<0.05). Streptomyces sp.4 is known to have potential benefits as a biological larvicidal agent.Abstrak: Daerah tropis memiliki tantangan besar kedepannya dalam pengendalian vektor demam berdarah dengue (DBD). Adanya kejadian resistensi pengendalian dengan zat kimiawi mendorong strategi pengembangan berbasis pengendalian biologis. Penelitian ini bertujuan untuk melakukan pengujian aktivitas kultur Streptomyces sp. sebagai larvasida A. aegypti. Seleksi Streptomyces sebagai biolarvasida dilakukan dengan uji aktivitas kitinase. Bakteri penghasil kitinase dilakukan kultivasi kultur biomassa untuk pengujian in vivo. Rancangan uji menggunakan Rancangan Acak Lengkap. Hasil penelitian dapat diisolasi 4 isolat Streptomyces yang diisolasi dari tanah berlumpur. Diantara keempat isolat, satu isolat yaitu Streptomyces sp.4 menunjukkan aktivitas kitinolitik sehingga digunakan untuk uji aktivitas larvasida secara in vivo. Hasil uji larvasida menunjukkan perlakuan kultur Streptomyces sp.4 berpengaruh nyata terhadap persentase kematian larva dibandingkan kontrol negatif (p<0.05) berdasarkan hasil uji Duncan. Persentase kematian tertinggi didapatkan pada perlakuan A6B1 yaitu sebesar 34.35%. Hasil uji Probit menunjukkan nilai LD50 dari kultur Streptomyces sp.4 adalah 24.6 ± 5.4 mL. Berdasarkan hasil uji in vivo diketahui bahwa perlakuan kultur cair Streptomyces sp.4 berpengaruh terhadap tingkat kematian larva A. aegypti dan berbeda nyata dengan kontrol negative (p<0.05). Streptomyces sp. 4 diketahui memiliki potensi sebagai salah satu agen larvasida biologis.